2017
DOI: 10.3390/w9090676
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of the Effect of Slenderness Effect on the Non-Darcy Groundwater Flow Characteristics in Bimsoils

Abstract: A series of experimental flow tests for artificial block-in-matrix-soils (bimsoils) samples with various slenderness ratios were performed to study the Non-Darcy groundwater flow characteristics. The variations of seepage velocity, permeability coefficient, critical sample height, and non-Darcy flow factor for samples against slenderness ratios were investigated. A servo-controlled flow testing system that was developed by the authors was adopted to conduct the flow test. Cylindrical bimsoil samples (50 mm dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In terms of non-Darcian flow, Wang et al [4] has conducted a series of experimental flow tests for bimsoils with various slenderness ratios. This study stated that the sample height had a strong influence on the flow characteristics of bimsoils, and the degree of non-Darcy flow decreased with the increase of sample height.…”
Section: Non-darcian Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of non-Darcian flow, Wang et al [4] has conducted a series of experimental flow tests for bimsoils with various slenderness ratios. This study stated that the sample height had a strong influence on the flow characteristics of bimsoils, and the degree of non-Darcy flow decreased with the increase of sample height.…”
Section: Non-darcian Flowmentioning
confidence: 99%
“…Also focusing on the experimental work of non-Darcian flow, like Wang et al [4], Chen et al [2] has conducted flow tests in synthetic single smooth and rough fractures. This study showed that non-Darcian Forchheimer flow was evident in both smooth and rough fractures, and it showed that the non-Darcian coefficient β c in the Forchheimer equation was most relevant for characterizing the heterogeneity of the rough single fractures.…”
Section: Non-darcian Flowmentioning
confidence: 99%
“…Recently, the studies on the fatigue behaviors of bimsoil have drawn engineers' attentions for the purpose of design and constructions. [8][9][10] Although detailed investigations have been performed on bimsoil via in situ testing, 11,12 laboratory compression test, 13 laboratory shear, 14 laboratory tension test, 15 or numerical tests, 16 mesoscopic testing using real-time acoustic emission and in situ CT scanning testing. 2,17 Most of the studies focused on the static loading paths.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, indoor tests represent the primary testing method of seepage indices for low-permeability materials. The indoor seepage testing methods for low-permeability materials have mainly evolved from the testing methods for high-permeability materials, including the anti-seepage grade measurement method of concrete [21,22], improved triaxial methods for seepage testing [23,24], and improved conventional methods for seepage testing [25][26][27][28]. These methods allowed upgrading the testing ability of seepage indices for low-permeability materials and promoted their engineering application.…”
Section: Introductionmentioning
confidence: 99%
“…However, the seepage flux had to be measured manually with a volume change tube by operating mechanical buttons [25]. In research on the slenderness influence of bimsoils on non-Darcy groundwater flow characteristics, a servo-controlled flux testing system was developed, but the seepage flux was still measured manually using a cylinder [26]. A pressure difference sensor helped build an experimental system for the permeability measurement of matrix particles of shale under a pore pressure up to 8 MPa, but the devices and the experimental process were complicated [27].…”
Section: Introductionmentioning
confidence: 99%